Development of an optimized ELISA and a sample preparation method for the detection ¿-actoglobulin traces in baby foods - Peláez Lorenzo, Cristina; Diez Masa, Jose Carlos; Vasallo, I.; de Frutos, Mercedes (My University, 2010)
Dairy products can induce allergic reactions even when present at very low levels, such as levels found in involuntary contamination during food manufacturing. ¿-Lactoglobulin (¿LG) is the main allergen in cow's milk. The objective of this work was to develop a sensitive method for ¿LG detection in baby foods through the optimization of an innovative sample preparation method. Three types of baby foods deliberately contaminated with dairy products or dairy desserts were sterilized to simulate the potential contamination occurring during manufacturing and then used as samples. Different sample preparation methods were compared. The best results were provided by an extraction solution containing ¿-mercaptoethanol, guanidine hydrochloride, and a saline solution. An ELISA method was optimized for the detection of ¿LG (LOD = 9.7 × 10-13 M). The developed method allowed detection of even 1 part of dairy product in 100,000 parts of baby food for some of the analyzed foods. © 2010 American Chemical Society.